2013
DOI: 10.1002/ijc.27990
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose gemcitabine depletes regulatory T cells and improves survival in the orthotopic Panc02 model of pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive human neoplasms with extremely poor prognosis and a low survival rate. Immunosuppressive cell populations, e.g. regulatory T cells (Treg), appear to be important in PDAC, contributing to patient's poor prognosis. Therefore, we investigated the PDAC microenvironment with a focus on conventional and regulatory T cells in view of their potential therapeutic importance. We found that tumors from the murine Panc02 orthotopic model of PDAC were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(129 citation statements)
references
References 54 publications
3
125
1
Order By: Relevance
“…Also other chemotherapeutic compounds may affect Tregs and immune suppressive myeloid cells. Gemcitabine is known to reduce both Tregs and MDSCs in mice and in patients with ovarian cancer [53,54,80,100,101]. A selective decrease in MDSCs was also observed after treatment with 5-fluorouracil (5-FU) [102].…”
Section: Administration Of Chemotherapy Before Vaccination Alleviatesmentioning
confidence: 99%
“…Also other chemotherapeutic compounds may affect Tregs and immune suppressive myeloid cells. Gemcitabine is known to reduce both Tregs and MDSCs in mice and in patients with ovarian cancer [53,54,80,100,101]. A selective decrease in MDSCs was also observed after treatment with 5-fluorouracil (5-FU) [102].…”
Section: Administration Of Chemotherapy Before Vaccination Alleviatesmentioning
confidence: 99%
“…The combination therapy also led to a decrease in the percentage of splenic MDCSs compared to immunotherapy (12. 16.66 § 2.71%, p < 0.05). In contrast, splenic Tregs were decreased in mice treated with the combined regimen (13.33 § 3.9%) compared to immunotherapy alone or the control treatment.…”
Section: E1095433-4mentioning
confidence: 87%
“…[16][17][18][19] In addition to its direct cytolytic activity on tumor cells, Gem was shown to induce the enhancement of T-cellmediated antitumor effects in pre-clinical studies. 20 Previously, we observed that the administration of recombinant lipoprotein-based vaccination as a monotherapy was not sufficient for therapeutic success in mice bearing advanced-stage tumors (3 1 cm diameter).…”
Section: Introductionmentioning
confidence: 99%
“…Immune tolerance is referred as the immunosuppressive capabilities of tumor-induced inhibitory cells which are mainly comprised of regulatory T cells (Treg), myeloid-derived suppressor cells (MDSC) and tumor-associated macrophages (TAM) [9]. Cyclophosphamide or gemcitabine with low dose treatment can selectively deplete Treg in patients with cancer or in tumor bearing mice [10]- [12]; Paclitaxel with noncytotoxic dose can inhibit MDSC and restore the anti-tumor activity of CD8 + T cells [13]; and 5-FU shows a pronounced effect on MDSC depletion [4]. Overall, approaches to deplete endogenous suppressive cell populations can improve the efficiency of anti-tumor immunity.…”
Section: Discussionmentioning
confidence: 99%